Creativity meets Cash: An unlikely pair? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
There has long been a perception that creativity and money are somewhat opposed to one another. Profitable artists are sometimes seen as sell-outs while risk-averse corporations are seldom regarded as centres of creativity. Yet, for survival, businesses need to be creative and the creative-types need to eat. In the book, Brainfruit: Turning creativity into cash from East to West, authors Hugh Mason and SMU associate professor Mark Chong provide a slew of practical ideas for anyone aspiring to build or understand the business of creativity.